A Decade of Brand Experience Research in Indonesia: Evolution, Patterns, and Future Directions - Sandra J.R. Kainde; Lefrand S. Pasuhuk; Deske W. Mandagi (Jurnal Economic Resource, 2026)
In contemporary branding and marketing scholarship, brand experience has become a pivotal construct for explaining how firms create value, cultivate loyalty, and maintain competitive advantage in increasingly digital and experience-intensive markets. Responding to this shift, the present study conducts a systematic literature review (SLR) to examine the evolution, intellectual structure, and thematic composition of brand experience research in the Indonesian context. Guided by the PRISMA framework, the review process screened 14,326 records retrieved from the Scopus database, resulting in a final sample of 132 peer-reviewed journal articles published between 2015 and 2025. Bibliometric and keyword co-occurrence analyses reveal five dominant thematic clusters: (1) core brand experience and relational outcomes, (2) brand management and brand equity formation, (3) digital and technology-mediated brand experience, (4) service quality and experience design, and (5) context-specific and market applications. The findings indicate that brand experience research in Indonesia has transitioned from early service quality and satisfaction-oriented perspectives toward more integrative, strategically grounded, and digitally enabled experiential frameworks. Despite this progression, several vital areas remain underdeveloped, including the emotional and psychological foundations of brand experience, the deeper integration of advanced analytics and artificial intelligence, ethical and cultural dimensions of experiential value, and the development of robust, context-sensitive measurement approaches. By synthesizing fragmented research streams into a coherent thematic structure, this study advances theoretical understanding of brand experience. It provides a structured foundation for future scholarly inquiry and managerial application in Indonesia and comparable emerging market settings.